Cross-reactivity and immunotherapeutic potential of BamA recombinant protein from Acinetobacter baumannii - Vieira de Araujo, Anna Erika; Conde, Luis Vidal; da Silva Junior, Haroldo Cid; de Almeida Machado, Lucas; Lara, Flavio Alves; Chapeaurouge, Alex; Pauer, Heidi; Pires Hardoim, Cristiane Cassiolato [UNESP]; Martha Antunes, Luis Caetano; D'Alincourt Carvalho-Assef, Ana Paula; Moreno Senna, Jose Procopio (Elsevier, 2021)
Acinetobacter baumannii is an important nosocomial pathogen. BamA is a protein that belongs to a complex responsible for organizing the proteins on the bacterial outer membrane. In this work, we aimed to evaluate murine immune responses to BamA recombinant protein (rAbBamA) from A. baumannii in an animal model of infection, and to assess cross-reactivity of this target for the development of anti-A. baumannii vaccines or diagnostics. Immunization of mice with rAbBamA elicited high antibody titers and antibody recognition of native A. baumannii BamA. Immunofluorescence also detected binding to the bacterial surface. After challenge, immunized mice demonstrated a 40% survival increase and better bacterial clearance in kidneys. Immunoblot of anti-rAbBamA against other medically relevant bacteria showed binding to proteins of approximately 35 kDa in Klebsiella pneumoniae and Escherichia coli lysates, primarily identified as OmpA and OmpC, respectively. Altogether, our data show that anti-rAbBamA antibodies provide a protective response against A. baumannii infection in mice. However, the response elicited by immunization with rAbBamA is not completely specific to A. baumannii. Although a broad-spectrum vaccine that protects against various pathogens is an appealing strategy, antibody reactivity against the human microbiota is undesired. In fact, immunization with rAbBamA produced noticeable effects on the gut microbiota. However, the changes elicited were small and non-specific, given that no significant changes in the abundance of Proteobacteria were observed. Overall, rAbBamA is a promising target, but specificity must be considered in the development of immunological tools against A. baumannii.
Keywords: Acinetobacter baumannii; BamA; Immunogenic; Resistant bacteria; Specificity